Application on bending performance of annular concrete-filled steel tube stent. (May 2020) - Zhang, Xiaonan; Zhang, Yi; Shan, Renliang; Bai, Yongtao; Zhang, Zhenhao
Abstract: Concrete filled steel tube (CFST) stent applied in the actual project is composed of four arc CFST arches with casting. By monitoring the uniform loading deformation of CFST arches mounted on the arc middle section and the left-right shoulder section in a CFST stent, a comprehensive analysis method was proposed for the flexural propagation using ABAQUS program for the strain and the ultimate strength capacity of the outer steel pipe and the confined core concrete. The realtime monitoring and experimental results show that, the CFST specimens were damaged under the influence of triple action of pulling, pressing and bending during the process of loading increases. The support resistance capacity of the annular CFST bracing system increases with the slip amount of CFST arches and gathering of the thickness of CFST stent. After reaching the ultimate load, although it leads to concrete volume expansion and then the steel tube drum package, but annular CFST bracing system reduced the bending moment damage deformation and meet the stability requirements of practical deep underground structure., therefore, there is a certain engineering guidance significance to the non-dense pressure construction condition. Highlights: A comprehensive analysis method was proposed for the concrete-filled steel tube (CFST) stent The strength capacity of the CFST stent increases with the gathering of the thickness of the arc A certain range of thickness for the gathering layer weakened the axial resistance of the stent in the CFST arch The boundary condition of different layers of the CFST support stent leads to better mechanical properties